2017
DOI: 10.1111/micc.12331
|View full text |Cite
|
Sign up to set email alerts
|

Flow motion dynamics of microvascular blood flow and oxygenation: Evidence of adaptive changes in obesity and type 2 diabetes mellitus/insulin resistance

Abstract: An altered spatial heterogeneity and temporal stability of network perfusion can give rise to a limited adaptive ability to meet metabolic demands. Derangement of local flow motion activity is associated with reduced microvascular blood flow and tissue oxygenation, and it has been suggested that changes in flow motion activity may provide an early indicator of declining, endothelial, neurogenic, and myogenic regulatory mechanisms and signal the onset and progression of microvascular pathophysiology. This short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 106 publications
0
28
0
2
Order By: Relevance
“…This may be attributable to an adaptive modulation of sympathovagal activity through which Sherpas can better regulate flow, allowing them to stay in a hypobaric atmosphere at lower temperatures without excessive autonomic stress (Passino et al, 1996). Declining spontaneous variation in flowmotion activity may be deleterious to health and has been identified in cardiovascular and metabolic disease (Clough, Kuliga, & Chipperfield, 2017). Despite significant differences in microvascular flux and function, our data showed little distinction in forearm tissue oxygenation between the cohorts at high altitude.…”
Section: Interpretation Of Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This may be attributable to an adaptive modulation of sympathovagal activity through which Sherpas can better regulate flow, allowing them to stay in a hypobaric atmosphere at lower temperatures without excessive autonomic stress (Passino et al, 1996). Declining spontaneous variation in flowmotion activity may be deleterious to health and has been identified in cardiovascular and metabolic disease (Clough, Kuliga, & Chipperfield, 2017). Despite significant differences in microvascular flux and function, our data showed little distinction in forearm tissue oxygenation between the cohorts at high altitude.…”
Section: Interpretation Of Resultsmentioning
confidence: 68%
“…In computational models, chaotic capillary activity has been shown to promote more efficient tissue oxygenation in skeletal muscle than regular rhythmic patterns of vasomotion (Pradhan et al 2007). Declining spontaneous variation in flowmotion activity may be deleterious to health and has been identified in cardiovascular and metabolic disease (Clough, Kuliga, & Chipperfield, 2017). Figure 1 demonstrates the changes in flowmotion control in both cohorts on ascent to altitude.…”
Section: Interpretation Of Resultsmentioning
confidence: 98%
“…Spectral analysis of the frequency components of the LDF signal has been shown to reflect the influence of endothelial (0.0095‐0.02 Hz) and sympathetic (0.02‐0.06 Hz) activity, myogenic activity in the vessel wall (0.06‐0.15 Hz), respiration (0.15‐0.4 Hz), and heart beat (0.4‐1.6 Hz) on local tissue perfusion . Variations in the amplitude and relative contribution of the spontaneous, rhythmic oscillatory fluctuations of both local (endothelial, neurogenic, and myogenic) and systemic origin have been associated with a decline in microvascular function in individuals at risk of, or with CV and Met disease . However, time and frequency domain analysis have not proved sufficient for the classification of tissue perfusion features in different pathophysiological groups or provided consistent interpretation of microvascular function.…”
Section: Introductionmentioning
confidence: 99%
“…Greater variability may also indicate an ability to influence flow independently of the spectral amplitude of flowmotion [16]. Thus a declining spontaneous variation in flowmotion activity as seen in vascular beds at risk of CV and Met disease [14] may contribute to a loss of system flexibility and adaptability in the face of physiological or pathological challenge.…”
Section: Complexity Of Network Perfusion and Oxygenation In Low Vsmentioning
confidence: 99%
“…Variations in the amplitude and relative contribution of these flowmotion oscillations have been associated with a decline in microvascular function in individuals at risk of CV and Met disease [9][10][11][12][13] (for review see [14]). Studies in a primate model of diabetes have shown a reduced complexity of the BF signal using a Lempel-Ziv (L-Z) complexity algorithm [15].…”
mentioning
confidence: 99%